2017
DOI: 10.24212/2179-3565.2017v8i2p104-125
|View full text |Cite
|
Sign up to set email alerts
|

Technical Solar Photovoltaic Potential of Scaled Parking Lot Canopies: A Case Study of Walmart U.S.A.

Abstract: Solar photovoltaic (PV) technology can provide sustainable power for the growing global population in cities, but it demands considerable land area. This is a challenge for densely populated cities. However, the stranded assets of non-productive parking lots areas can be converted to solar farms with PV canopies, enabling sustainable electricity generation while preserving their function to park automobiles. This study provides a method for determining the technical and economic potential for converting a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…From Walmart parking lot area (Aw) which is 21,000 m 2 67 and packing factor (PF) which is 170 W/m 2 the PV size ( P sw ) calculated is 3.57 MW. The PV system size is thus constrained by the parking lot area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Walmart parking lot area (Aw) which is 21,000 m 2 67 and packing factor (PF) which is 170 W/m 2 the PV size ( P sw ) calculated is 3.57 MW. The PV system size is thus constrained by the parking lot area.…”
Section: Methodsmentioning
confidence: 99%
“…Big‐box retailers such as Walmart, Kohl's, Costco, Staples, Target and IKEA are already covering their rooftops with PV and are familiar with the techno‐economic optimization process of meeting their own electrical demands 61‐66 . However, the parking lots of such retailers present an additional opportunity as medium‐scale solar farms, far exceeding in store demands 67 . Thus, retail stores could provide an anchor for an aggressive distribution of microgrids in North America.…”
Section: Introductionmentioning
confidence: 99%
“…Stakeholders and residents will play critical roles in such decision-making processes. For instance, large commercial customers such as Walmart [129] can be a host to municipal EV charging stations through a carefully developed memorandum of understanding.…”
Section: Policy Implications and Future Workmentioning
confidence: 99%
“…Kahn & Kok (2014) showed that Walmart stores use less electricity per store than comparably large stores in other retail chains. Krishnan et al (2017) documented the widespread implementation of solar panels on Supercenter roofs and discussed the feasibility of extending solar panels to parking lots. Tan et al (2018) studied Walmart's use of blockchain technology, itself a topic of growing relevance in food and agriculture, to reduce food waste and the company's carbon footprint.…”
Section: Other Economic Impactsmentioning
confidence: 99%